2021
DOI: 10.5194/hess-25-2399-2021
|View full text |Cite
|
Sign up to set email alerts
|

Global ecosystem-scale plant hydraulic traits retrieved using model–data fusion

Abstract: Abstract. Droughts are expected to become more frequent and severe under climate change, increasing the need for accurate predictions of plant drought response. This response varies substantially, depending on plant properties that regulate water transport and storage within plants, i.e., plant hydraulic traits. It is, therefore, crucial to map plant hydraulic traits at a large scale to better assess drought impacts. Improved understanding of global variations in plant hydraulic traits is also needed for param… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 112 publications
1
38
0
Order By: Relevance
“…Our finding that constraining a process-based model with hydrologic flux data can yield ecologically consistent vegetation parameter values is in agreement with other recent work (Knighton, Kuppel, et al, 2020;Knighton, Singh, & Evaristo, 2020;Kuppel et al, 2018a;Liu et al, 2021;Peaucelle et al, 2019). Model sensitivity analysis further indicated that δ XYLEM data can support estimation of plant trait values related to rooting, stomatal conductance, growth temperatures, and possibly tree water storage (Figure 3).…”
Section: Plant Trait Estimation From δ Xylem Observationssupporting
confidence: 91%
“…Our finding that constraining a process-based model with hydrologic flux data can yield ecologically consistent vegetation parameter values is in agreement with other recent work (Knighton, Kuppel, et al, 2020;Knighton, Singh, & Evaristo, 2020;Kuppel et al, 2018a;Liu et al, 2021;Peaucelle et al, 2019). Model sensitivity analysis further indicated that δ XYLEM data can support estimation of plant trait values related to rooting, stomatal conductance, growth temperatures, and possibly tree water storage (Figure 3).…”
Section: Plant Trait Estimation From δ Xylem Observationssupporting
confidence: 91%
“…Ultimately, the accuracy of such inferences likely inherently depends on the relative sensitivity and information content of different observations, including the VWC estimates. Nevertheless, some early applications of data assimilation with remotely sensed VWC estimates show this approach has promise (Liu et al, 2021 ; Liu et al, 2021 ). In each of these studies, observations at two times a day were used, but a more complete diel cycle may act as an even stronger constraint.…”
Section: Inferring Belowground Activity From Aboveground Vwc Observat...mentioning
confidence: 99%
“…Among common model inversion techniques (e.g., frequentist methods or Kalman filter [Mo et al., 2008]), we select Markov Chain Monte Carlo (MCMC) for parameter estimation, primarily because it quantifies the epistemic uncertainty associated with each model parameter in addition to its best estimates (Wu et al., 2014). It has also been successfully used for inversion of PHMs in eddy covariance (Liu et al., 2020) and remote sensing (Liu et al., 2021) settings. In our case, we use MCMC to estimate the whole‐plant effective values of plant hydraulic traits as parameters in a physiologically informed sap flow model using local soil water potential and atmospheric conditions as inputs to the model.…”
Section: Introductionmentioning
confidence: 99%